Working Capital Management Strategies In The Manufacture Sector, Systematic Literature Review - Faisal Riza Rahman; Sugeng Wahyudi (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This study aims to investigate the trends in existing studies in the field of working capital management in the context of capital markets in terms of definitions, theories, themes, and methodologies. Working capital is one of the principal drivers of value in a company. This research is a systematic literature review conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis method, which is carried out systematically by adhering to the correct stages or research protocols with the Scopus database. A total of 30 articles were published in 24 journals from 2018-2023 were selected. This study used systematic data to reveal trends in working capital, quantitative analysis, and literature review to define relevant themes within the topic. The most research on working capital management strategies is in European countries, Ireland, Czech Republic, Hungary, Slovakia, Poland, Russia, and Eastern Europe, namely 36.7%. This shows that there is still little similar research in the Southeast Asia region. Most are still looking for a correlation between working capital management and company performance as proxied by return on assets (ROA). Implementing efficient working capital management is a key factor in the success of a company's business, especially in the manufacturing sector which depends on working capital funding.